Pengaruh Manajemen Operasi di Era Digital Terhadap Penjualan pada E-Commerce - Hanie Supandi (Jurnal Publikasi Ilmu Manajemen, 2024)
Operations are defined as activities that manage production factors to create products to add value through the transformation process. However, to remain competitive in an increasingly dynamic market, e-commerce companies must optimize their operations, especially in logistics, inventory, and customer service management. This can be seen from the ease of people in meeting their needs, especially with the existence of modern markets around the community. The research method used is library research which focuses on collecting and analyzing secondary data from various relevant literature sources. In this context, the sources used include books, journal articles, research reports, and other related documents. Furthermore, the collected data is systematically analyzed to identify patterns, trends, and gaps in previous research. Operations management in e-commerce in Indonesia faces various complex challenges. One of the main problems is related to logistics and shipping. Inadequate infrastructure in various regions, especially in remote areas, causes long delivery times and significantly increased logistics costs. In addition, inventory management is also a significant challenge. Operational management of E-Commerce sales has several Structural Aspects or Regulatory Aspects, Operational Aspects, Operations Management Systems.